Protein profiling of Candida albicans planktonic and biofilm cultures upon exposure to Aureobasidin / Komathy Munusamy - Komathy, Munusamy (2019)
Candidiasis is a fungal infection leading to significant morbidity and mortality in immunocompromised patients. Aureobasidin (AbA), a cyclic depsipeptide antifungal drug, has been reported to be effective against Candida albicans but is yet to be used for therapy. Although AbA is presumed to target the fungal sphingolipid biosynthesis, the exact mechanism of action has yet to be defined. As a prerequisite to study the mechanism of action of this antifungal drug, this study investigated changes in the proteome of planktonic and biofilm cultures of C. albicans upon exposure to AbA. In this study, the whole cell extracts of biofilm and planktonic cultures of C. albicans strain SC5314 pre- and post-exposure to AbA were subjected to liquid chromatography mass spectrometry (LC-MS/MS) analysis. Using sequence homology search tool (SPIDER) of PEAKS software (ver. 7.5), proteins were identified based on the setting of at least one unique peptide matched and a significance (-10lgP) value of >20. The proteome prior to AbA exposure demonstrated a total of 203 and 533 proteins from the planktonic and biofilm cultures, respectively, with a false discovery rate of ≤1%. The biological process, molecular function, and subcellular localization of biofilm and planktonic proteins were annotated using Go Slim Mapper of the online Candida Genome Database. Classification of biological processes demonstrated greater differences in the number of biofilm proteins associated with the regulation of biological processes (n=65), organelle organization (n=57), transport (n=55), stress response (n=47), filamentous growth (n=30), chemical response (n=30), lipid metabolism (n=23) and carbohydrate metabolism (n=20) compared to planktonic culture. As for molecular function, no major difference was observed in both cultures, iv with approximately 10-20% of the proteins are associated with hydrolase, transferase and protein binding activities. On subcellular localization, 68.7 and 66.4% proteins of planktonic and biofilm cultures were predicted to be localized in cytoplasm. A total of 293 and 374 proteins were annotated in the AbA-treated planktonic and biofilm cultures with sub-inhinbitory AbA concentration (1 µg/ml) for 2.5 hours. A lower percentage of proteins annotated for organelle organization in the AbA-treated planktonic culture (18.1%) as compared to the dimethyl sulfoxide (DMSO)-treated planktonic culture (23.2%). There was a 5% increase in the proteins annotated for translation in AbAtreated planktonic culture. AbA-treated biofilm culture has shown reduction in the percentages of proteins annotated for vesicle-mediated transport (from 8.4 to 5.3%) and filamentous growth (15.8 to 12.8%), and an increase in the percentage of proteins annotated for carbohydrate metabolic process (8.2 to 12.0%). The regulation of cellular amide metabolic process and actin cytoskeleton organization are two biological processes shared by AbA-treated planktonic and biofilm cultures. This study also reviewed some C. albicans proteins which are annotated for pathogenesis, biofilm formation, lipid metabolic process and filamentous growth in response to AbA. Further exploration of the drug-affected proteins may aid in the search for potential drug target in the treatment of candidiasis.